FAKTOR-FAKTOR PENYEBAB KEJADIAN STUNTING DI DESA ULAK PATIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU PROVINSI RIAU TAHUN 2021 - Siana, Yusti; Amran, Rika; Mhd Nurhuda; Dian Puspita; Siti Rahmi, Nur Haji (Nusantara Hasana Journal, 2024)
Stunting is a condition of growth and development failure in toddlers due to chronic malnutrition that causes children to be too short for their age. Low nutritional intake is a direct cause of nutritional health problems in stunted children. Rokan Hulu Regency is included in the highest stunting locus in 2019-2020 and Ulak Patian Village is one of the villages in Rokan Hulu Regency that is a stunting locus. Objective: To determine the factors causing stunting in Ulak Patian Village, Kepenuhan District, Rokan Hulu Regency, Riau Province in 2021. Method: The scope of this study is child health science. This research was conducted from August 2021 to December 2022. The population in this study were all children aged 24-36 months in Ulak Patian Village, Kepenuhan District, Rokan Hulu Regency, Riau Province, as many as 40 samples with a total sampling technique. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using the chi-square test, data processing using the computerized SPSS program version IBM 25.0. Results: The most common gender of children is male, namely 24 children (60%), the most common birth weight of children is low birth weight (LBW) namely 21 children (52.5%), the most common level of maternal education is not graduating from elementary school namely 21 mothers (52.5%), the most common socio-economic level of families is low socio-economic namely 23 children (57.5%) and the most common nutritional status of children is malnutrition as many as 18 children (45%). There is no relationship between gender and the incidence of stunting (p = 0.519). There is a relationship between birth weight, maternal education level, socio-economic level and nutritional status with the incidence of stunting in children aged 24-36 months in Ulak Patian Village. Conclusion: From the factors causing stunting in Ulak Patian Village, Kepenuhan District, Rokan Hulu Regency, Riau Province, there is almost a relationship between birth weight, education level, socio-economic level and nutritional status with the incidence of stunting